2023
DOI: 10.3390/ijms24021192
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Ruminal Acidosis as a Potential Factor that Induces Endometrium Injury in Sheep

Abstract: The demand for economic benefits has led to an increase in the proportion of high-concentrate (HC) feed in the ruminant diet, resulting in an increased incidence of subacute ruminal acidosis (SARA). During SARA, a high concentration of lipopolysaccharide (LPS) translocated in the rumen induces a systemic inflammatory response. Inflammatory diseases, such as endometritis and mastitis, are often associated with SARA; however, in sheep, the mechanism of the effect of SARA on the endometrium has rarely been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Cows diagnosed with SARA often exhibit low pH levels and elevated concentrations of free LPS in the rumen, which if not treated properly can trigger a proin ammatory response [51,52]. When the ruminal epithelium is in amed, a decrease in barrier function increases the chance for pathogenic substances, including LPS, to enter the blood circulation and negatively affect other organs such as the liver, udder and uterus [6, 53,54]. The present in vitro data con rmed that LPS has a negative impact on TJ proteins such as ZO-1 and Occludin and that EGCG (10, 20 and 50 μM) can reverse this negative effect.…”
Section: Discussionmentioning
confidence: 99%
“…Cows diagnosed with SARA often exhibit low pH levels and elevated concentrations of free LPS in the rumen, which if not treated properly can trigger a proin ammatory response [51,52]. When the ruminal epithelium is in amed, a decrease in barrier function increases the chance for pathogenic substances, including LPS, to enter the blood circulation and negatively affect other organs such as the liver, udder and uterus [6, 53,54]. The present in vitro data con rmed that LPS has a negative impact on TJ proteins such as ZO-1 and Occludin and that EGCG (10, 20 and 50 μM) can reverse this negative effect.…”
Section: Discussionmentioning
confidence: 99%
“…As widely recognized, a high-concentrate diet can easily lead to an increased incidence of sub-acute ruminal acidosis (SARA) in cows, consequently resulting in an abnormally high concentration of lipopolysaccharides (LPSs) in the blood [ 21 ]. SARA-induced LPS translocation triggers endometrial inflammatory responses, resulting in damages to the endometrial epithelial barrier and physiological dysfunction, severely affecting the productivity of ruminants, and the elevated LPS levels can induce oxidative stress, trigger severe inflammatory responses, and even impact embryo implantation [ 24 , 25 ]. When examining the uteri of cows with endometritis, we observed oxidative stress in the endometrial tissue, accompanied by a significant increase in apoptosis factors.…”
Section: Discussionmentioning
confidence: 99%
“…Subacute ruminal acidosis (SARA) is a common nutritional metabolic disease caused by feeding highgrain diets to improve the milk production performance of dairy cows [1][2][3]. Investigators have revealed that SCFAs and lactic acid accumulation inducing low rumen pH of SARA leads to gram-negative bacteria death, lysis and lipopolysaccharide (LPS) release, thereby destroying the rumen epithelium barrier integrity by triggering an in ammatory response in the rumen epithelium, then causing systemic in ammation [4][5][6]. Speci cally, research found that a high concentration of ruminal LPS, which is a characteristic of SARA, facilitates to activation of the NF-κB and MAPKs in ammatory pathways, and promotes pro-in ammation cytokines production in the rumen epithelium [7,8].…”
Section: Introductionmentioning
confidence: 99%